Experiment study on mechanical properties of sand-doped bentonite. Issue 3 (March 2020) - Cao, Yupeng; Zhang, Rui; Xu, GuiZhong; Zhang, Shuai; Xu, Jianwen
Abstract: Bentonite is a special soil with water expansion and water loss shrinkage properties, which is widely used as backfill material. In order to explore the effect of sand content on the properties of Bentonite, compaction test, wL (liquid limit) and wP (plastic limit) test, direct shear test and permeability test were taken to analyse the compaction, hydrophilic, shear characteristics and permeability of sand-blended bentonite. The results show that as the amount of bentonite increases, wop (the optimal water content), wL, wP and IP (plastic index) of sand-doped bentonite increase, the Pdmax (the maximum dry density) and cohesion increase first and then decrease, the angle of internal friction decreases gradually. When bentonite content is less than 20%, increasing the content of bentonite has significant effect on reducing coefficient of permeability.